Synthesis of azo compounds by nanosized iron-promoted reductive coupling of aromatic nitro compounds - Moglie, Yanina Fernanda (2008)
Treatment of a variety of aromatic nitro compounds with the active-iron based reducing system composed of FeCl2·4H2O, an excess of lithium powder and a catalytic amount of 4,4´-di-tert-butylbiphenyl (DTBB, 5 mol%) in THF at room temperature, led to the formation of the corresponding symmetrically substituted azo compounds in good yield, resulting from a reductive coupling process. Some other functionalities including carbonyl, halogen, amino and hydroxyl groups, demonstrated to be compatible with the reaction conditions, giving none reduced or coupled by-products. In all cases, the azo compounds formed have not experienced over-reduction to the corresponding hydrazo or amino derivatives even upon prolonged heating or using an excess of the reducing system.